ENSURING THE BUDGET EFFICIENCY OF TERRITORIES: THEORETICAL AND APPLIED CONCEPT - Vakhovych, I.; Kupyra, M.; Nedopad, G. (Socio-economic relations in the digital society, 2022)
The article substantiates the essential aspects of budget efficiency of the territory, which form the conceptual foundations of the studied issues and determine its theoretical and applied concept. The risks of decentralization and challenges from the standpoint of budget efficiency of territories systematized, and the factors of influence through the level of management, the number of resources and the nature of the partnership are identified.Based on the methods of economic synthesis, generalization, analysis and comparison, the level of budget efficiency of territories by areas analyzed. These are economic efficiency, fiscal efficiency, social efficiency, efficiency of budget investment. This allowed us to identify the main factors of supply and unite regions with high, medium, low levels of budget efficiency.The territories of Ukraine were grouped according to the level of budget efficiency, which allowed identifying gaps that were taken into account to eliminate negative trends. In particular, regions with low levels of industrial development and high levels of agricultural specialization are characterized by low levels of budget efficiency. This situation leads to a decrease in financial self-sufficiency and inability to balance local budgets due to a lack of additional tax revenues. At the same time, a number of regions were identified that have provided an average level of budget efficiency but show a downward trend in the integrated index. A group with a low level of budget efficiency needs to develop practical steps to strengthen its strengths and empower local budgets. This is the growth of tax and non-tax revenues and optimization of expenditures aimed at the efficient use of budget funds.A differentiated approach to the formation of strategic decisions of financial management of territories is proposed. Which allowed to develop a systematic strategy with the definition of components of budget efficiency and to form an architecture of types of financial management strategies. As a result, it will strengthen the weaknesses of each region. The components of ensuring budget efficiency are very important because efficiency is the result of dividing resources, which is the basis of economic science. In the complex, such processes will increase the budget potential and appeal to financial capacity, sustainability, and efficiency.
Keywords: efficiency; budget efficiency; decentralization; strategy; financial management; financial resources